Effect of PITX2 gene polymorphism on growth traits in Awassi ewes - Bayraktar, M; Alkhammas, A; Mohammed, T (Journal of the Hellenic Veterinary Medical Society, 2024)
Genetics and environment influence quantitative traits. Several genes contribute to sheep's productive traits, including the paired-like homeodomain transcription factor 2 (PITX2). Therefore, the research investigated whether productive traits of Awassi ewes are associated with birth type and PITX2 gene variability. Two hundred and thirty-two ewes aged three to four years were studied (123 singleton ewes and 109 twin ewes). Phenotypic analysis was conducted by measuring body weight and body dimensions. Sheep genomic DNA was extracted and subjected to genotyping and sequencing to confirm the presence of variants derived from amplification of exon 5 of PITX2. A 382-bp amplicon displayed three genotypes, CC, CT, and TT. A comparison of PITX2 genotypes and birth types with productive traits showed that CC-type ewes had significantly heavier live body weights, birth weight, and higher body dimensions compared to CT-type and TT-type ewes. The CC genotypes were recorded strongly positive correlation with birth type, live body weight, height at back, width at shoulder, width at pelvic, chest width, and abdomen width ((r=0.81, P=0.02), (r=0.77, P=0.04), (r=0.97, P=0.02), (r=0.98, P=0.02), (r=0.96, P=0.03), (r=0.92, P=0.03), and (r=0.98, P=0.01) respectively. Sheep of the CC genotype had higher live body weights and body measurements, making them more productive. These findings provide valuable insight into the characteristics and functions of the PITX2 gene for the future of sheep breeding.